2000
DOI: 10.1152/ajplung.2000.279.1.l5
|View full text |Cite
|
Sign up to set email alerts
|

[Ca2+]i oscillations regulate type II cell exocytosis in the pulmonary alveolus

Abstract: Pulmonary surfactant, a critical determinant of alveolar stability, is secreted by alveolar type II cells by exocytosis of lamellar bodies (LBs). To determine exocytosis mechanisms in situ, we imaged single alveolar cells from the isolated blood-perfused rat lung. We quantified cytosolic Ca(2+) concentration ([Ca(2+)](i)) by the fura 2 method and LB exocytosis as the loss of cell fluorescence of LysoTracker Green. We identified alveolar cell type by immunofluorescence in situ. A 15-s lung expansion induced syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
124
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(131 citation statements)
references
References 42 publications
(63 reference statements)
5
124
2
Order By: Relevance
“…It has been suggested that AEC I contribute to the regulation of surfactant secretion in AEC II (Ashino et al, 2000;Isakson et al, 2003;Patel et al, 2005). However, the factors in AEC I that mediate AEC I and AEC II communication are unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that AEC I contribute to the regulation of surfactant secretion in AEC II (Ashino et al, 2000;Isakson et al, 2003;Patel et al, 2005). However, the factors in AEC I that mediate AEC I and AEC II communication are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In situ fluorescence imaging has shown that interalveolar Ca 2+ conductance initiates in AEC I and stimulates extrusion of lamellar bodies from AEC II (Ichimura et al, 2006). Moreover, Ca 2+ oscillations from AEC I communicate with AEC II during lung inflation, suggesting a role for AEC I in surfactant secretion (Ashino et al, 2000). However, the mediators for AEC I and AEC II communication are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The gas exchange barrier is composed of ATI and endothelial cells joined by fused basement membranes. ATI cells are important in the regulation of alveolar fluid balance and surfactant secretion by ATII cells in response to stretch [7][8][9][10]. ATII cells cover the remaining 2-5% of the lung9s surface area.…”
mentioning
confidence: 99%
“…Along with the work in [29][30][31][32], this manuscript highlights the role of Cx43 in mediating calcium waves. The paper shows that Cx43-made gap junctions contribute to endothelial cell expression of adhesion molecules for leukocytes.…”
mentioning
confidence: 87%
“…It is important to note that transmission of calcium waves from type I to type II cells can also occur via paracrine stimulation of purinergic receptors through ATP release [30,31]. These calcium signals may also help to adjust surfactant production to stimuli such as changes in pulmonary blood pressure [32,33]. Furthermore, GJIC also enables calcium wave propagation from one alveolus to the next [29], as demonstrated by in situ fluorescence microscopy analysis of the intact lung.…”
Section: Functions Of Connexins In Lungmentioning
confidence: 99%